The beginnings of the modern philosophy of music in England : Francis North's A philosophical essay of musick (1677) with comments of Isaac Newton, Roger North and in the Philosophical transactions /: Francis North's A philosophical essay of musick (1677) with comments of Isaac Newton, Roger North and in the Philosophical transactions. (2016) - Kassler, Jamie Croy
No abstract available